Understanding of Development Emergency Medical Services in Laos Emergency Medicine Residents - Apiratwarakul, Korakot; Celebi, Ismet; Tiamkao, Somsak; Bhudhisawasdi, Vajarabhongsa; Pearkao, Chatkhane; Ienghong, Kamonwon (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Rising death tolls from traffic accidents are quickly becoming an inescapable problem in almost all countries around the world. That being said, the World Health Organization has launched an ambitious campaign aimed at reducing the death rate from traffic accidents by 50% in the next 10 years. Development of emergency medical services (EMSs) was the tool to success the goals, especially in low- to middle-income countries including Laos. However, no studies regard perspective of training EMS in Laos emergency medicine residents. AIM: The aim of our work is to demonstrate the effect of EMS training for Laos emergency medicine residents to the development of the national policy in Lao’s EMS. METHODS: A cross-sectional study was conducted in two countries (Laos and Thailand) from January 2020. The project activities were establishment of a command-and-control center, development of EMS support system, and training for emergency care professionals. RESULTS: The eight Laos emergency medicine residents were enrolled between January and March 2020. After practicing as a dispatcher and emergency medical consultant in Thailand at Khon Kaen University, the participants from Laos found that all personnel gained experience and improved their knowledge of technology in EMS and organization management. This had a direct impact on improving confidence in their return to practice in Laos. CONCLUSIONS: The human resource development through international collaboration between Thailand and Laos is contributing the effective knowledge and expertise learning in Laos. Moreover, the result of this training may provide the most effective care system resulting in the much-needed drop in the mortality rate of traffic accidents in Laos.